Introduction to the Special Issue "Sport for Social Inclusion: Critical Analyses and Future Challenges" - Haudenhuyse, Reinhard (Social Inclusion, 2015)
“Sport for Social Inclusion: Critical Analyses and Future Challenges” brings together a unique collection of papers on the subject of sport and social inclusion. The special issue can be divided into three major parts. The first part consists of three papers tacking on a broad perspective on sport and social exclusion, with specific attention to austerity policies, sport-for-change and exclusion in youth sports. The second part of the special issue tackles specific themes (e.g., group composition and dynamics, volunteering, physical education, youth work, equality, public health) and groups (e.g., people with disabilities, disadvantaged girls, youth) in society in relation to sport and social exclusion. The third part consists of three papers that are related to issues of multiculturalism, migration and social inclusion. The special issue is further augmented with a book review on Mike Collins and Tess Kay’s Sport and social exclusion (2nd edition) and a short research communication. The editors dedicate the special issue to Mike Collins (deceased).